1996
DOI: 10.1002/anie.199619491
|View full text |Cite
|
Sign up to set email alerts
|

Prominent Gelation and Chiral Aggregation of Alkylamides Derived from trans‐1,2‐Diaminocyclohexane

Abstract: max.,~inin. residual elccti-on density: 0.64, -0 3 2 eA -3 . Crqst;illogr;iphic data (excluding structure factors) for the structure aepoi-ted in this paper have been deposited with the Cambridge Crystallographic Data Centre as supplementary pnhlication no. CCDC-179-63. Cope5 o l tho data can be ohtaincd l'ree of chnrge on application to The Director. CCDC. 12 Union Ro;td.Cambridge CB2 IEZ, U K (fax: Int. code +(1223) 336-1133: e-mail:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
305
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 452 publications
(312 citation statements)
references
References 22 publications
6
305
1
Order By: Relevance
“…10-30 nm in diameter and several micrometers in length, which eventually form developed nanofiber networks. From the scanning electron and atomic force microscopic analyses, we found that no remarkable, helically twisted fiber morphologies 170,171 are observable (Figure 26). In order to get further insight into the molecular packing and orientation within the nanofibers, we measured X-Ray diffraction of a freeze-dried hydrogel of 25 (20).…”
Section: Nanofiber Formation From Nucleotide-appended Bolaamphiphilicmentioning
confidence: 99%
“…10-30 nm in diameter and several micrometers in length, which eventually form developed nanofiber networks. From the scanning electron and atomic force microscopic analyses, we found that no remarkable, helically twisted fiber morphologies 170,171 are observable (Figure 26). In order to get further insight into the molecular packing and orientation within the nanofibers, we measured X-Ray diffraction of a freeze-dried hydrogel of 25 (20).…”
Section: Nanofiber Formation From Nucleotide-appended Bolaamphiphilicmentioning
confidence: 99%
“…The sol-gel transcription method [7] using gelators and lipids is a simple and powerful method to control the morphological shapes of 1D nanostructures. Especially, chiral gelators and lipids can form helical morphological shapes [8]. Up to now, the helical structures in organogel fibers [9] and self-assemblies of lipids [10] have been successfully transcribed into inorganic silica and titania.…”
Section: Introductionmentioning
confidence: 99%
“…The diamide derivative 3 24 and diurea derivative 4 25 are both synthesized in one step reaction from trans-(1R,2R)-diaminocyclohexane ( Figure 3). Compounds 3 and 4 are excellent gelators comparable to L-isoleucine derivative 1.…”
Section: Cyclohexane-based Gelatorsmentioning
confidence: 99%